(untitled) (World Bulletin of Public Health, 2025)
According to the World Health Organization (WHO) for 2019, 10 million people in the world are infected with tuberculosis, including 5.6 million men, 3.2 million women and 1.2 million children. It is estimated that 1 million children worldwide suffer from tuberculosis every year. The reduction in the incidence rate from 2015 to 2019 was 9%, and the global goal for 2030 was 80%. Therefore, the main task of anti-tuberculosis and practical work is to prevent the development of tuberculosis lung lesions, including in comorbidity and especially against the background of the pandemic growth of COVID-19 among the population. Only on the basis of screening and "targeted" formation of groups of low, medium, high and very high risk of COVID-19 patients for tuberculosis lung lesions and modern implementation of primary, secondary or tertiary prevention measures can solve this currently extremely urgent task